Rehabilitasi dan Renovasi Sarana Prasarana Sekolah Kabupaten Nunukan - Tahan, Tahan (Jurnal Teknologi Berkelanjutan, 2023)
Establish and develop high-quality human resources in border areas, both in terms of mastery and ability of science and technology, competitiveness, and the formation of national character, feelings, and attitudes. Improving School Infrastructure manifests the Government's attention to Improving Educational Infrastructure in the 3 T (Frontier, Outermost, Disadvantaged) Regions. Good implementation management of the Nunukan Regency School Facilities and Infrastructure Rehabilitation and Renovation work has impacted the construction completion on time and with the right quality. Implementing the work method aims to provide knowledge about the stages from the tender process to the Handover of Work. The process of carrying out construction work for the Rehabilitation and Renovation of School Facilities and Infrastructure in Nunukan Regency has the challenge of managing worker mobilization, material mobilization, and technical personnel mobilization, which is divided into 9 spread-out location points, as well as geographical locations on 2 islands and directly bordering the State of Malaysia. As well as limited stock materials available at the work location.